The musician chair - Yin, Jiayi (2018)
To set up for an instrumental performance, handling on stage equipment is a significant part during preparation. Be it a solo guitar performance, a Chinese Orchestra concert or School Bands playing for competitions, items such as the music stand, the foot rest and the chair are often necessities. Due to the variety of equipment, handling multiple items is a not an easy task most of the time. With limited space on stage, moving or adjusting these equipment simultaneously require extra effort and care in order to prevent hits and drops. This is especially so for performers when they are already holding their instruments in hand. For off-stage crews dealing with storage and transportation, it is difficult as well when the items are in large quantity. In addition, general chairs and stools are commonly used for these performance occasions, many are not best suit in terms of playing ergonomics and visual presentation. Considering the aspects of furniture design in context for instrumental performance, this project will explore the possibilities to provide solutions to these issues, improving the overall user and visual experiences.